2015
DOI: 10.1259/dmfr.20140235
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint diagnostics using CBCT

Abstract: The present review will give an update on temporomandibular joint (TMJ) imaging using CBCT. It will focus on diagnostic accuracy and the value of CBCT compared with other imaging modalities for the evaluation of TMJs in different categories of patients; osteoarthritis (OA), juvenile OA, rheumatoid arthritis and related joint diseases, juvenile idiopathic arthritis and other intra-articular conditions. Finally, sections on other aspects of CBCT research related to the TMJ, clinical decision-making and concludin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
138
2
22

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(164 citation statements)
references
References 102 publications
2
138
2
22
Order By: Relevance
“…[1][2][3][4][5][6] As the CBCT is an X-ray-based device, the dense materials of hard tissues (i.e. bone and tooth) absorb more radiation energy than soft tissues (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] As the CBCT is an X-ray-based device, the dense materials of hard tissues (i.e. bone and tooth) absorb more radiation energy than soft tissues (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The type of morphology of the condyle on imaging creates an initial environment, which is continuously modified throughout life based on the type of mastication of the individual and also due to the fact that this acts as a primary growth centre 10 . Diagnosis of the degenerative changes affecting the TMJ can be done more accurately using CBCT which provides images at a lower exposure than CT 2 The results of our study revealed that in coronal section, convex morphology was more commonly observed(49%) followed by round(23%).This was in accordance with the study conducted by Yale et.al(1966) 5 .…”
Section: Discussion:-mentioning
confidence: 99%
“…Em contrapartida, a TCCB limita-se apenas a avaliação dos componentes ósseos, e ao diagnóstico de alterações presentes nas estruturas ósseas da ATM, ou seja, o mesmo não é indicado para avaliar tecidos moles dessa articulação 21 . Dessa forma, quando for necessária a avaliação por imagem dos tecidos moles, nos casos de lesões, o exame de escolha deve ser inicialmente a RM, assim como, para diagnosticar possíveis alterações e/ou lesões da ATM, a TCCB será indicada somente quando essas alterações estiverem comprometendo os componentes ósseos dessa articulação Além disso, alguns autores destacam que, mesmo apresentando limitações, a RM e a TCCB representam, quando associados, métodos de imagem importantes para diagnosticar alterações tanto nos componentes ósseos quanto nos tecidos moles da ATM 8 .…”
Section: Podeunclassified